Religious Self Report in the Use of Social Media: Improved Counseling Guidance Services - Raja Rahima Munawarah Raja Ahmad; Rahmatul Aufa; Irawati; Nurul Zahrotunnisa; Hasgimianti (Bisma The Journal of Counseling, 2023)
Social media has become the most popular platform in recent years. The high level of access and easy access to various content allows teenagers to use social media excessively and unwisely, so it is necessary to instill religious values in teenagers as natural self-control. Efforts to instill religious values need to be assisted by instruments that are able to measure the religious level of adolescents so that educational designers such as guidance and counseling teachers and Islamic religious education teachers can plan appropriate materials and types of services. The aim of this study is to develop an instrument in the form of a self-report with a Likert Scale model and is non-test in nature. This study uses an R&D approach through the 10 stages of the Borg & Gall development model. Participants numbered 509 teenagers of junior high school age, who were taken using random samples. The reliability test has been carried out using the Alpha Cronbach formula and to see the validity and level of match between items and indicators, Confirmatory Factor Analysis has been used through the Structural Equating Modeling application. The indicators that have been used to measure the religious level of teenagers are Faith, Islam, and Ihsan according to the Muslim History Hadith. The results of the analysis have shown that 30 items are valid, fit and reliable and have fulfilled the practical objectives of preparing the instrument, namely that it can be done in a short time and is easy to do without help from other parties.